Capture of carbon dioxide in metal organic frameworks - Abid, Hussein Rasool (Curtin University, 2012)
This scholarly research investigates synthesis of different Zr-MOFs and some of Al- MOFs and studies their charcateristics and applications in capture or separation of carbon dioxide. CO2 is consdered as a main gas in greenhouse gases which have caused global warming.This thesis takes into account of using modified synthesis and activation procedures toward improving MOF affinity to adsorb CO2 and reducing its heat of adsorption. Also, the dynamic adsorption capacities were calculated for some Zr-MOFs and Al- MOFs from breakthrough experiments.Zr-MOF, Zr-MOF-NH4, Zr-MOF-NH2, Zr-MOF-NO3, and Zr-MOF-NO2 were obtained during direct synthesis process while MIL-53, and amino-MIL-53 were synthesized according to previous procedures with some modifications in activation process and MIL-96 was synthesized and activated by a new procedure.A fine crystalline powder of Zr-MOF was solvothermally synthesized and activated by chloroform and methanol separately. Chloroform activation was more vigorous to enhance surface area; the BET surface area was 1434 m2 g-1 which is higher than that of samples in methanol activation and previously reported. The Zr-MOF was stable up to 753 K. Chloroform activated Zr-MOF presented CO2 adsorption capacity of 79 and 45 cc g-1 at 1 atm, 273 and 302 K, respectively. Also, the heat of CO2 adsorption was around 28 kJ mol-1. However, the separating factor of CO2/CH4 was higher for methanol activated Zr-MOF although the adsorption capacity was lower.Ammonium hydroxide was used as an additive in the synthesis process to modify the pore size. Zr-MOF-NH4-2 showed the largest pore size; it was 2.3 nm. It was found that this modification has a negative impact on the CO2 adsorption capacity at STP. However, the adsorption capacity increased at increasing pressure over 5 atm(8.63 mmol g-1 at 987 kPa) while the heat of adsorption was 22 kJ/mol (which was calculated at 1 atm at the coverage of 5- 29 cc/g). In addition, Zr-MOF-NH4-1 and Zr-MOF-NH4-3 were more selective to separate CO2 from CO2-CH4.Amino-Zr-MOF was thermally stable up to 623K. In addition, its surface area was lower than Zr-MOF-(Parent). On the other hand, CO2 adsorption capacity was higher, giving 100 cc g-1 (4.46 mmol) at 273K and 1 atm. Also, it showed 9 mmol g-1 at 273K and 988 kPa.Another modification in direct synthesis process was achieved using nitric acid as an additive or using NO2-functionalised linker. NO3-modified samples exposed thermal stability the same as Zr-MOF (Parent), they may be decomposed at 773K. However, Zr- MOF-NO2 decomposed at 623K. Nitric acid additives played a main role in enlarging the pore size and reducing crystal size. Zr-MOF-NO3 exposed lower CO2 adsorption at STP with increasing amount of the additives. Zr-MOF-NO3-1 and Zr-MOF-NO3-2 presented adsorption capacities of 61.4 and 57.9 cc g-1 respectively, while Zr-MOFNO3- 2 had the lowest heat of adsorption of 17.8 kJ/mol. Conversely, Zr-MOF-NO2 revealed an adsorption capacity of 74.7 cc g-1 and the heat of adsorption was 37 kJ/mol. However, Zr-MOF-NO3 samples exposed higher CO2 adsorption capacity at high pressure. Also, the selectivity of CO2/CH4 was the highest on Zr-MOF-NO3-2.Al-MOF exposed different thermal stability. MIL-53, MIL-96 and amino-MIL-53 were stable up to 773, 570, and 650K respectively. MIL-96 exposed higher CO2 adsorption as 124 cc g-1 at STP while amino-MIL-53 has lower value at 48 cc g-1. However, amino- MIL-53 demonstrated heat of adsorption of 28 kJ/mol. Also, MIL-53 displayed the highest dynamic adsorption (169 cc g-1 at 1 bar and 304K).